Komunikasi Budaya dan Transformasi Opini Publik : Studi Kasus Hastag #FreePalestine - Salim, Nurul Anisa (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2023)
This study involves an in-depth analysis of Cultural Communication and Public Opinion Transformation through a case study of the hashtag #FreePalestine on social media. The Israeli-Palestinian controversy set the stage for a significant shift in public opinion, and these hashtags became an important instrument in weaving complex online narratives. The aim of this research is to understand the impact of Cultural Communication through the hashtag #FreePalestine in transforming public opinion. Her focus includes online mobilization, influence on policy, changing international perceptions, and the formation of activist movements. This research method uses a mixed approach, combining qualitative and quantitative analysis. Social media analysis is conducted to track trends, sentiment, and networks of relationships, while interviews and surveys are used to gain a deeper understanding of the influence of these opinion transformations in the real world. This research shows that the hashtag #FreePalestine not only creates change in online opinion, but also mobilizes real action and shapes global narratives that influence policy and business. Cultural communication on social media is key to understanding further impact, with image visualization and visual solidarity being key elements in changing public opinion.